Cochlear implantation in congenital cochlear abnormalities - Raja Lope Ahmad, Raja Ahmad Al'konee; Saim, Lokman (Malaysian Medical Associations, 2005)

(untitled)
Many children have benefited from cochlear implant device including those with congenital malformation of the inner ear. The results reported in children with malformed cochlea are very encouraging. We describe 2 cases of Mondini’s malformation with severe sensorineural hearing loss. Cochlear implantation was performed and both of them underwent post-implantation speech rehabilitation. Post-implantation both of them were noted to respond to external sound. But the second case developed facial twitching a few months after the device was switched on. It is important to evaluate the severity of the inner ear deformity and the other associated anomalies in pre-implantation radiological assessment in order to identify the problem that may complicate the surgery and subsequent patient management.